(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to “reveal the most important modern techniques that were used in the plastic art of post-modern drawings.” To achieve the goal of the research, the researcher used the descriptive approach on a sample of artistic works, “post-modern drawings”. The research sample consisted of (3) works from post-modern schools. Modernity according to the sequence mentioned in the theoretical framework. The research tool was a form for analyzing artistic works. To reach the research results, the researcher used a set of (statistical methods, including: the Cooper equation to find out the percentage of agreement between the arbitrators and between the arbitrators and the researcher. The weighted mean equation: This equation was used to find out the reliability rates. The (Percentage Weight) equation. This equation was used to find out the percentage weights for each paragraph. The study showed: Based on the results reached by the researcher, a set of conclusions are as follows: 1- Postmodern arts have relied on culture, concepts and ideas that did not exist in the eras that preceded them 2- Postmodern arts employed technological, industrial, technological, informational, advertising, media, and fashion developments to create works that formulate the forms of these arts. 3- Postmodernism declared its loyalty to the artistic form in the face of the decline in content and substance, and the concepts of replacement, difference, metaphor, and circulation became the most present concepts in the form of artistic work according to systems created by action in real time. Based on the results of the study, the researcher recommended several recommendations, including: 1- Highlighting the aesthetic features of postmodern arts and trying to impart them to art education students, which contributes to the diversity and enrichment of their artistic productions. 2- The necessity of making field visits to some international virtual museums that highlight aesthetic techniques to learn about them closely, and to encourage the issuance of publications, pamphlets, and artistic and aesthetic studies that address the concept of beauty and expression in post-modern drawings. 3- The need to encourage students to make similar practical applications that are compatible with the traditions of our society, to open the way for them to use and experiment with new materials, not for the purpose of imitation, but to expand their perceptions and knowledge. In continuation of the study, the researcher proposed a number of proposals, including: 1- Computer technologies and their use in post-modern arts.2- Technology in postmodern graphics 3- Modern critical approaches and their implications for post-modern arts.